Os centros de atenção psicossocial infantojuvenis e o cuidado a crianças e adolescentes com transtorno do espectro autista e suas famílias - Lourenço, Mariane Cristina (2020)
The Brazilian health service called “Psychosocial Care Centers for children and adolescents” (Centros de Atenção Psicossocial Infantojuvenis - CAPSij) are the first initiative to include autism in the field of public Mental Health in Brazil. The intense discussions that take place between people who advocate for CAPSij as a possible care service for this population and people who advocate for a care based in specialized clinics highlight the need to understand about the potentialities and challenges of the care offered for people with autism and their families in CAPSij. This research aimed to understand the potentialities and the limits of the care offered for children and adolescents with Autism Spectrum Disorder (ASD) at CAPSij. This study used a mixed-methods approach and was developed in two stages. The first stage had the participation of managers from the four CAPSij located in Campinas city/São Paulo state and sought to characterize children and adolescents with ASD inserted in the four CAPSij located in this county, as well as to identify the care actions developed with this people. The data were collected through the application of a questionnaire to service managers and the consultation to medical records. The second stage,was developed an Etnography srudy, which enabled a greater approximation and understanding of the studied phenomenon. For this stage, technicians, family members, children and adolescents with ASD, and other actors linked to a CAPSij located in the same city collaborated. The main instrument of data harvest was the Filed Journal. Besides this, another resources like interviews, photographic records and the consultation to medical records were used. We sought to know and understand CAPSij's everyday life in more depth, especially regarding to the care offered to children and adolescents with ASD and their families, identifying the potentialities and limits of this health equipment and of this kind of care. The main results of Step 1 revealed that children and adolescents with ASD correspond to approximately 30% of CAPSij users. Regarding the age of users with ASD in the four CAPSij, the number of children was considerably larger than the number of adolescents. Among the main care actions mentioned by the managers are: individual assistance in speech therapy, occupational therapy and psychology, group sessions, besides listening and assistance for the families. As main challenges, the managers pointed out the scarcity of resources, the complexity of demands inserted in the CAPSij, the difficulty of articulating network care, and the difficulty in thinking about the care for adolescents with ASD. In Step 2 the maisn results revealed contless potentialities such as: the welcoming and caring offered for the families; the space for free movement and meeting with different people, favored by the “Ambience” device; the actions and articulations with the territory; the continuous training of professionals in Primary Health Care through “Matrix Support”; and the development of actions in different territory’ spaces. One of the perceived challenges is the complex issue of the diagnosis, sought by many families as a guarantee of access to rights, but which creates labels and stigmas. Another important challenge revealed is the difficulty that the CAPSij has in establishing partnerships with other intra and intersectoral equipment that could offer specialized care to people with ASD, breaking with the excludent posture and increasing the range of possibilities that can be differential for the expansion of the contractual power, engagement, and social inclusion of these people. In conclusion, this study have achieved its goals. The results contribute for reflexions and improvement of care actions destinated for people with ASD inserted in the CAPSij and in the Psychosocial Care Network as a whole.